(untitled) (Journal of Parents and Teachers, 1995)
It emphasizes the historical importance of the island of Alexandria, especially its lighthouse and the library, as centers of knowledge and culture. Reflections by poets and philosophers on the sun and the moon are mentioned, symbolizing the duality of life. In general, themes of light, knowledge and influence on humanity are explored.